Dari Kolektor Besi Tua Hingga Sosok Religius: Stereotip Orang Madura Melalui Humor - Herlianto A. (Deskripsi Bahasa, 2019)
This research aims to describe the stereotype of Madurese through humor. Humor and stereotyping are two inseparable concepts, especially ethnic humor. Madurese humors are discourses that are not neutral; there are interests and intentions behind every discourse of humor that is set. Ethnic humor is formed by exploring the weaknesses of other ethic groups especially related to the character of the ethnic. This is a form of speaker superiority about the ethnic. This study uses a social paradigm, qualitative approach, and interviewing and observing data collection methods. Source of the data comes from documents and informants. Data were analyzed by applying critical discourse analysis of van Dijk. This theory divides a discourse into three part: text, social cognition and context. The results showed at least seven of Madurese stereotypes through humor. Of the seven, it is divided into two categories, which are based on the job: scrap metal collectors, female herbalist, religious man, and satay seller; and based on the characters, namely: dumbness, cleverness, and rudeness. This critical research proves the stereotype through humor is an attempt to perpetuate the culturally alienated position of Madurese race.